Diagnostic reliability of Widal slide agglutination test for enteric fever- still a query - Yadav, Kiran; Parihar, Geeta; Yadav, Suresh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Typhoid fever is a major public health problem associated with significant morbidity and mortality in many countries. The Widal slide agglutination test is a commonly used test for diagnosing enteric fever. Limited literature is available on its diagnostic ability in comparison to the tube agglutination test. Aim of this study was carried out to evaluate the efficacy of the Widal slide agglutination test for the diagnosis of enteric fever. Methods: This cross-sectional study was done in department of microbiology in Jawahar Lal Nehru medical college and hospital, Ajmer over a period of six months from September 2013 to March 2014. A total of 640 serum samples received in the microbiology department were processed for detecting the presence of anti O and anti H agglutinins against S. typhi, S. Paratyphi A and S. Paratyphi B by slide and tube Widal agglutination tests as per standard protocols. The significant titre for O and H agglutinin, 1:160 was taken as positive. Results: Of the 154 slide Widal positive samples, 115 (18%) samples tested negative by the tube agglutination test whereas only 39 (6%) samples were positive by both slide and tube agglutination. Conclusions: Slide Widal test has high sensitivity and NPV (100%) can be used as a screening tool but due to low specificity (83.93%) any positive sample should be confirmed by tube Widal test.